Optimalisasi Pelatihan Daur Ulang Sampah Menjadi Gelar Karya di SD Negeri Purwakarta Cilegon - Deni Sunaryo; Berliana Febriyanti; Dian Denta Alumi; Fahaina Izzatul Jannah; Ratu Bintang Apriliani; Yoga Adiyanto; Dhany Isnaeni Darmawan (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2024)
Waste is one of the biggest environmental problems in Indonesia. Based on data from the 2014 Central Statistics Agency (in Angga & Djunaidi, 2017) it shows that Indonesia produces around 187.2 million tons of waste / year and is in second place as the largest waste producer in the world. Waste not only comes from households but also from the school environment. If this waste is left unchecked, it can cause disease. This large amount of waste is also caused by people's lack of concern for the environment. Therefore, it requires an appropriate management strategy, one of which is through recycling. The waste recycling training aims to increase knowledge of dealing with plastic waste and develop the creativity of Purwakarta State Primary School teachers so that they are able to process waste into learning media as well as capital for students to understand learning more easily through waste recycling training. Implementation methods include environmental observation, problem identification, determining service activities, coordinating service activities with prospective participants, implementing training. The waste recycling training activity has been successful and running smoothly, able to develop creativity and increase teachers' knowledge regarding waste managent.